2016
DOI: 10.1371/journal.pone.0146716
|View full text |Cite
|
Sign up to set email alerts
|

When Friends’ and Society’s Expectations Collide: A Longitudinal Study of Moral Decision-Making and Personality across College

Abstract: Early adulthood is a developmentally important time period, with many novel life events needing to be traversed for the first time. Despite this important transition period, few studies examine the development of moral decision-making processes during this critical life stage. In the present study, college students completed moral decision-making measures during their freshman and senior years of college. Results indicate that, across four years, moral decision-making demonstrates considerable rank-order stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
1
4
0
2
Order By: Relevance
“…Nevertheless, we might expect similar findings in a female, non-college sample, as more modern samples show mostly similar personality development patterns across gender and college attendance (Lüdtke, Roberts, DEVELOPMENT OF SELF-CONCEPT 24 Trautwein, & Nagy, 2011). Moreover, a study of moral development within this dataset found similar findings to more modern dataset (Bollich et al, 2016). Another limitation is the coding of self-statements.…”
Section: Limitationssupporting
confidence: 70%
“…Nevertheless, we might expect similar findings in a female, non-college sample, as more modern samples show mostly similar personality development patterns across gender and college attendance (Lüdtke, Roberts, DEVELOPMENT OF SELF-CONCEPT 24 Trautwein, & Nagy, 2011). Moreover, a study of moral development within this dataset found similar findings to more modern dataset (Bollich et al, 2016). Another limitation is the coding of self-statements.…”
Section: Limitationssupporting
confidence: 70%
“…This prediction is based on the test-retest stability of personality traits such as agreeableness and conscientiousness (Fleeson, 2001; Roberts & DelVecchio, 2000), which are related to behaving morally (Cohen, Panter, Turan, Morse, & Kim, 2014; Matsuba & Walker, 2004). Furthermore, studies examining explicitly moral constructs have shown that the rank-order stability of individual differences in moral judgments is relatively high (Bollich, Hill, Harms, & Jackson, 2015; Graham et al, 2011). Although most of this work relies on self- or other-reports of traits rather than observed behavior, it nevertheless provides grounds for predicting stable individual differences in moral behavior.…”
Section: Present Studymentioning
confidence: 99%
“…3 Though see Forbes (2018), Bollich et al (2016), Hofmann et al (2014), Lee and Holyoak (2020), and Weidman et al (2020). 4 Relatedly, for favourable judgements, we predict the opposite effect.…”
Section: Moral Categorization Involving Known Othersmentioning
confidence: 60%